2017
DOI: 10.1088/1742-6596/815/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Plasma airflow jets diagnosis by means of time-resolved tomography

Abstract: Abstract. A simple optical arrangement combining a single high-speed CCD camera and a set of mirrors has been setup to record simultaneously light intensity of atmospheric air plasma jet issued from multiple directions. The adopted approach is presented and its potential benefit to examine plasma emission in 3D is outlined. Rebuild local emission distributions are briefly analyzed for two typical jet exhibiting different flow structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Rathore et al [189] reported a prototype of an automatic tomographic diagnostic system for real-time monitoring and control of a microwave-induced plasma torch, and they used a detector assembly that consisted of 8 cameras at 45°angular distance, which covered a 360°view, and a filtered backprojection algorithm. In 2017, Babou et al [190] demonstrated that the 3-D structure of plasma airflow can be reconstructed using a single imaging device. Five images obtained for different projection angles were taken by using a combination of a high-speed CCD camera and four tilted mirrors, and additional images were generated (resampling) via trigonometric interpolation for the Radon transform.…”
Section: Imaging Techniques (3-d or Cross-sectional)mentioning
confidence: 99%
“…Rathore et al [189] reported a prototype of an automatic tomographic diagnostic system for real-time monitoring and control of a microwave-induced plasma torch, and they used a detector assembly that consisted of 8 cameras at 45°angular distance, which covered a 360°view, and a filtered backprojection algorithm. In 2017, Babou et al [190] demonstrated that the 3-D structure of plasma airflow can be reconstructed using a single imaging device. Five images obtained for different projection angles were taken by using a combination of a high-speed CCD camera and four tilted mirrors, and additional images were generated (resampling) via trigonometric interpolation for the Radon transform.…”
Section: Imaging Techniques (3-d or Cross-sectional)mentioning
confidence: 99%